The valorization of GMOs and the de-valorization of farmers’ contributions to biodiversity—Synthesis paper - Wesley Tourangeau; Chelsea Smith (Canadian Food Studies, 2015)
Genetically modified organisms (GMOs)are deeply contested with respect to their implications for food security and environmental sustainability. The three papers in this section effectively capture the present-day focal points of the debates over the undeniably vast topic area of genetic resources and agricultural biotechnology and their implications for food security and the environment. Noah Zerbe outlines the value of (and contestation over) plant genetic materials and rights to their use. Matthew Schnurr explores the current push into a second wave of genetically modified (GM) crops, particularly focused on developing countries. And Taarini Chopra looks back at 20 years of experience with commercialized GM crops, focusing on GM technology’s consistent failure to address issues of food security.